STUDI FENOMENOLOGI PERILAKU MAHASISWA PENGGUNA KRS ONLINE - Purwati, Ria Ayu; Nuraina, Elva; Yusdita, Elana Era (Widya Mandala Surabaya Catholic University, 2021)
Based on the phenomenon of lack of confidence when programming KRS online, the research was conducted to describe the perceptions of students of class 2016 using KRS Online on the Management Information System of Universitas PGRI Madiun related to payment bill information and to show how confident they are to use so that it affects their behavior. The study was conducted on students from 2016 with 7 informants from 3 faculties, namely FKIP, FEB and FT. The method used is qualitative with a phenomenological approach and data collection by means of interviews and participant observation. The results show that student behavior as seen from the perceived usefulness has a relaxed attitude and is not complicated, responsive and fast, willing to use it alone without having to be represented shows that students feel comfortable. Behavior that can be seen from the perception of ease of being confident, more relaxed, cautious, not confused because of clear steps. The perceived convenience and usefulness could be factors that affect the smoothness of UNIPMA’s revenue.